Progress and prospects in symmetrical solid oxide fuel cells with two identical electrodes - Su, Chao; Wang, Wei; Liu, M.; Tadé, Moses; Shao, Zongping (Wiley-VCH Verlag, 2015)
Symmetrical solid oxide fuel cells (SOFCs) have attracted increasing attention due to their potential for improved thermomechanical compatibility of the electrolyte and the electrodes, reduced fabrication cost, and enhanced immunity to coking and sulfur poisoning. While the electrode materials of symmetrical SOFCs are initially limited to those with stable phase structures under both reducing and oxidizing atmospheres, many novel electrode materials are currently being developed and investigated that may undergo a beneficial phase transition or reduction in a reducing atmosphere, although the same material may be used initially for the construction of both anode and cathode. Here, the advances made in the development of electrode materials and structures for symmetrical SOFCs are summarized, including single-phase electrodes, multi-phase (composite) electrodes, and those that are reducible upon exposure to a reducing atmosphere. The electrical conductivity, thermomechanical properties, and redox behavior of these electrode materials, together with their performance and stability in different SOFCs, are discussed and analyzed. The problems associated with different types of symmetrical SOFCs are outlined and the materials that show promise as symmetrical electrodes are highlighted, offering critical insights and useful guidelines for knowledge-based rational design of better electrodes for commercially viable symmetrical SOFCs.